In Situ Detection of Lithium‐Ion Battery Pack Capacity Inconsistency Using Magnetic Field Scanning Imaging. Issue 3 (13th January 2022) - Wang, Hang; Dai, Lang; Mao, Lei; Liu, Yongbin; Jin, Yi; Wu, Qiang
Abstract: One of the main obstacles for the reliability and safety of a lithium‐ion battery pack is the difficulty in guaranteeing its capacity consistency at harsh operating conditions, while the key solution is accurate detection of cell capacity inconsistency within the battery pack without taking it apart for destructive testing. Here, an in situ and nondestructive technology is proposed for this purpose, by imaging the magnetic field of the battery pack during its operation, the minor current imbalance within the pack can be identified without strong interference of the magnetic susceptibility due to state of charge change, and the corresponding location can also be determined. The feasibility of employing this technique in the battery pack with multicells is also demonstrated, which is beneficial in practical systems for evaluating the battery pack reliability, with which mitigation and maintenance can be taken to extend its remaining useful life. Abstract : Magnetic field scanning imaging is a key tool in in situ detection of a lithium‐ion battery pack. The influence of cell current and magnetic susceptibility on the magnetic field changes is first discussed and then the detection technique for battery pack capacity inconsistency is proposed. The feasibility and practicality of employing this technique in the battery pack with multicells is demonstrated.